2018
DOI: 10.3233/nre-172357
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of educational interventions for children and adolescents with acquired brain injury

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Conflicts of interest:The authors report no conflicts of interest. Cochrane Collaboration's Risk of Bias tool was used to assess systematic error in the included studies. Results: Four studies met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…All these deficits cause a negative impact on children's adjustment in daily life [13]. Consequently, rehabilitation treatments to improve cognitive and behavioral functioning have been considered necessary for sustaining recovery and adjustment of these patients [12, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these deficits cause a negative impact on children's adjustment in daily life [13]. Consequently, rehabilitation treatments to improve cognitive and behavioral functioning have been considered necessary for sustaining recovery and adjustment of these patients [12, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, numerous papers on rehabilitation treatments for pediatric ABI or reviews on the topic have been published [1, 12, 1420]. However, it has not been yet clarified which are the most effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Linden, Glang, and McKinlay [7] performed a systematic review and meta-analysis, using randomized control trial (RCT) class I studies, to examine educational interventions for children with ABI. While three studies met their meta-analysis criteria, there were no significant differences between educational intervention and control conditions on academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis indicated that remote CCT programs based on the repetition of cognitive exercises (drill-based exercises) have an effect on the visual-spatial abilities of children with ABI, but no effects were documented for other cognitive abilities 26 . Nevertheless, evidence of the effects on far transfer measures of CCT programs for children with ABI has been questioned 29,30 . Overall, contrasting results on CCT efficacy have been reported in the literature and no clear indication of which training format is optimal (i.e., training performed under the guidance of a healthcare practitioner or independently; training intensity and duration; one-or multi-domain stimulation etc.)…”
mentioning
confidence: 99%